The Implementation of Electronic Medical Records on Performance through Nurses' Workload and Completeness of Nursing Care Documentation - Danar Rudiantoro; Sentot Imam Suprapto; Agustin Agustin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Effective nursing care services are an indicator of healthcare service quality. The use of electronic medical records (EMRs) plays a crucial role in improving the quality of nursing care services. Complete and accurate nursing care documentation has significant implications for the quality of nursing care provided. Objective: This study aims to analyze the impact of implementing electronic medical records on nurses' performance through nurses' workload and the completeness of nursing care documentation. Method: This study employed a quantitative research design with a cross-sectional approach. A total sampling technique is applied involving 85 respondents as the sample. Data analysis was conducted using path analysis to determine the relationships between research variables. Results: Statistical regression tests (Model 1 and Model 2) showed that the implementation of electronic medical records significantly affects nurses' workload, the completeness of nursing care documentation, and nurses' performance. Path analysis results indicated that electronic medical records have a direct impact on nurses' performance (0.225). Additionally, the effect of electronic medical records on nurses' performance through workload was 0.178, while its effect on performance through the completeness of nursing care documentation was 0.108. Conclusions: The study concludes that there is no significant indirect effect of electronic medical record implementation on nurses' performance through workload and completeness of nursing care documentation.